Capacity Planning for High-Traffic Events in Cloud Environments - Venkata Narasimha Sagar Gandha, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Cloud capacity planning for high-traffic events has become crucial for modern digital businesses facing unprecedented challenges during seasonal sales, product launches, and viral marketing campaigns. Organizations must implement robust strategies to handle sudden traffic surges while maintaining system stability and user experience. Advanced technologies including artificial intelligence, machine learning, and edge computing enable precise demand forecasting, dynamic resource allocation, and real-time monitoring. These capabilities, combined with automated scaling mechanisms and comprehensive security measures, allow businesses to optimize costs while ensuring consistent performance during peak loads. The integration of cloud-native tools and platforms further enhances operational efficiency through predictive analytics and automated resource management, making it possible for organizations to build resilient systems capable of handling extreme traffic variations while maintaining high availability and customer satisfaction.
Keywords: Capacity Planning; Cloud Computing; Edge Computing; Resource Optimization; Scalability